International Symposium on Electromagnetic Compatibility - EMC EUROPE 2012
DOI: 10.1109/emceurope.2012.6396758
|View full text |Cite
|
Sign up to set email alerts
|

High power microwave tests of media converters

Abstract: We report on high power microwave (HPM) susceptibility tests of vulnerable IT network components. The devices under test are five different commercial and industrial media converters, one military media converter and a shielded enclosure for commercial media converters. The report compares results of susceptibility tests in different configurations supplemented by transfer function measurements

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…As a consequence, more and more electronic control and communication systems (Supervisory Control and Data Acquisition System, SCADA) are integrated to support the grid management. These devices can be considered as gateways for EMI (Electromagnetic Interference) and IEMI (Intentional Electromagnetic Interference) [1], [2]. Initial investigations of smart meter devices showed their high susceptibility to HPEM [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a consequence, more and more electronic control and communication systems (Supervisory Control and Data Acquisition System, SCADA) are integrated to support the grid management. These devices can be considered as gateways for EMI (Electromagnetic Interference) and IEMI (Intentional Electromagnetic Interference) [1], [2]. Initial investigations of smart meter devices showed their high susceptibility to HPEM [3].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the failure of single such devices or even clusters has no effect on the power grid as a whole [3]. The tests of smart meters [3] provided first predictions of coupling paths into systems realized with these components together with a generic wiring similar as in earlier tests of media converters [2]. The results of studies concerning coupling paths into a generic office wiring setup showed that the direct coupling through device housing apertures becomes dominant for frequencies above 2 GHz [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation